2016
DOI: 10.1017/s0890060416000068
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming design fixation: Design by analogy studies and nonintuitive findings

Abstract: Design fixation is a phenomenon with important significance to many fields of design due to the potential negative impacts it may have in design outcomes, especially during the ideation stage of the design process. The present study aims to provide a framework for understanding, or at least probing, design fixation by presenting a review of existing defixation approaches, as well as metrics that have been employed to understand and account for design fixation. This study also describes the results of two desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 84 publications
(186 reference statements)
1
48
0
Order By: Relevance
“…We compared these fixation rates (for this first individual brainstorming phase only) in a 2 × 2 ANOVA with problem and fixation source as between group variables, and the ratio of similar concepts to total number of concepts per student (in phase 1) as the dependent measure. This fixation ratio was used to account for the varied concept set sizes generated across students [16]. The results showed a main effect of fixation source where more fixation occurred in the self-generated example condition (M = 0.32, SD = 0.24) than in the Provided Example condition (M = 0.24, SD = 0.28), F(1, 165) = 4.4, p < 0.04.…”
Section: Hypothesis 1: Providing Examples Leads To More Fixationmentioning
confidence: 99%
See 3 more Smart Citations
“…We compared these fixation rates (for this first individual brainstorming phase only) in a 2 × 2 ANOVA with problem and fixation source as between group variables, and the ratio of similar concepts to total number of concepts per student (in phase 1) as the dependent measure. This fixation ratio was used to account for the varied concept set sizes generated across students [16]. The results showed a main effect of fixation source where more fixation occurred in the self-generated example condition (M = 0.32, SD = 0.24) than in the Provided Example condition (M = 0.24, SD = 0.28), F(1, 165) = 4.4, p < 0.04.…”
Section: Hypothesis 1: Providing Examples Leads To More Fixationmentioning
confidence: 99%
“…If designers cling to initial examples because generation is challenging, using generation tools as support may reduce fixation. Previous studies have explored design-by-analogy tools to support idea generation and shown that fixation effects from presented examples can be reduced [15,16]; however, these studies included a 2-day delay between an initial generation phase and a second phase with the support tool. Is it possible to mitigate design fixation within a design session?…”
Section: -2 / Vol 142 October 2020mentioning
confidence: 99%
See 2 more Smart Citations
“…That is, each word or phrase of the acronym can be applied to a product or part to trigger potential reuses. Moreno et al (2016) observed SCAMPER's effectiveness in generating novel concepts, since reflecting on each corresponding word or phrase could provide novel insights.…”
Section: B Scampermentioning
confidence: 98%